2021
DOI: 10.1186/s12879-021-05904-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial resistance profiles of respiratory microbial flora in African children with HIV-associated chronic lung disease

Abstract: Background HIV-associated chronic lung disease (CLD) is common among children living with HIV (CLWH) in sub-Saharan Africa, including those on antiretroviral therapy (ART). However, the pathogenesis of CLD and its possible association with microbial determinants remain poorly understood. We investigated the prevalence, and antibiotic susceptibility of Streptococcus pneumoniae (SP), Staphylococcus aureus (SA), Haemophilus influenzae (HI), and Moraxella catarrhalis (MC) among CLWH (established on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 61 publications
4
18
4
Order By: Relevance
“…Nasopharyngeal (NP) swabs and sputa were collected from participants at baseline, 48- and 72-week visits. Details of sample collection, handling and transport, culture and antibiotic susceptibility testing (AST) for SP, SA, HI and MC have previously been described [ 10 ]. Briefly, susceptibility to AZM, tetracycline and cotrimoxazole was conducted for all four bacterial species using the Kirby–Bauer disk diffusion method.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nasopharyngeal (NP) swabs and sputa were collected from participants at baseline, 48- and 72-week visits. Details of sample collection, handling and transport, culture and antibiotic susceptibility testing (AST) for SP, SA, HI and MC have previously been described [ 10 ]. Briefly, susceptibility to AZM, tetracycline and cotrimoxazole was conducted for all four bacterial species using the Kirby–Bauer disk diffusion method.…”
Section: Methodsmentioning
confidence: 99%
“…42) 0.81 [0.47-1.42] 0.469 #Missing values: Weight-for-age-z-score(5), Viral load suppression at enrolment(5), ART regimen(1), Duration of ART at baseline(10), BMI-for-age z-score (5), Height-for-age z-score(5). *Missing values: Weightfor-age-z-score (3), Viral load suppression at enrolment (1), Duration of ART at baseline (4), BMI-for-age z-score (3), Height-for-age z-score(3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We previously observed that a Haemophilus, Moraxella or Neisseria (HMN)-dominant sputum bacteriome was associated with a 1.5-fold increased risk of HCLD, compared to a Streptococcus or Prevotella-dominant bacteriome [10]. We also showed an association between HCLD and respiratory carriage of Streptococcus pneumoniae and Moraxella catarrhalis [11]. The therapeutic effect of AZM in COPD may be mediated by changes in the lung bacteriome along with associated changes in microbial metabolites that interact with the host immune system [2].…”
Section: Introductionmentioning
confidence: 85%
“…Detailed microbiological procedures and results have been reported previously [7,8]. Conventional culture was performed for common bacterial pathogens at baseline, 12 and 18 months on sputum and nasopharyngeal samples.…”
Section: Methodsmentioning
confidence: 99%